An efficient method to synthesize novel 5-O-(6′-modified)-mycaminose 14-membered ketolides. Issue 2 (14th January 2016) - Wang, A-Peng; Liu, Chao; Yang, Shuang; Zhao, Zhehui; Lei, Pingsheng
Abstract: A new and facile procedure was developed to synthesize novel 5- O -(6′-modified)-mycaminose 14-membered ketolides by adopting different protective strategies and comparing various glycosylation conditions. Seven trichloroacetimidate donors which had different types of substituent groups at C-6 position were synthesized to couple with the erythronolide. Nine novel 5- O -(6′-modified)-mycaminose 14-membered ketolides were obtained to verify the utility of the method. Graphical abstract: